2018
DOI: 10.3390/catal8060247
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Real World Soot-Catalyst Contact Conditions for Lab-Scale Catalytic Soot Oxidation Studies

Abstract: In diesel soot oxidation studies, both well-defined model soot and a reliable means to simulate realistic contact conditions with catalysts are crucial. This study is the first attempt in the field to establish a lab-scale continuous flame soot deposition method in simulating the “contact condition” of soot and a structured diesel particulate filter (DPF) catalyst. The properties of this flame soot were examined by means of X-ray diffraction (XRD) and transmission electron microscopy (TEM) for structure analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…To find out the major active species for the photocatalytic oxidation, several scavengers were added in the photocatalytic system individually to trap and remove corresponding active species. It was reported that ammonium oxalate (AO), isopropanol (IPA), and N 2 could act as effective scavengers to holes (h + ), hydroxyl radical (●OH), and superoxide radical (●O 2 − ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. As shown in Figure 8 , the photodegradation activity of the g-C 3 N 4 /ZnO (0.1:1 CN) sample had a dramatic decrease with the addition of AO and N 2 under light irradiation, suggesting that both holes and ●O 2 − are the main oxidative species in a MB degradation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To find out the major active species for the photocatalytic oxidation, several scavengers were added in the photocatalytic system individually to trap and remove corresponding active species. It was reported that ammonium oxalate (AO), isopropanol (IPA), and N 2 could act as effective scavengers to holes (h + ), hydroxyl radical (●OH), and superoxide radical (●O 2 − ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. As shown in Figure 8 , the photodegradation activity of the g-C 3 N 4 /ZnO (0.1:1 CN) sample had a dramatic decrease with the addition of AO and N 2 under light irradiation, suggesting that both holes and ●O 2 − are the main oxidative species in a MB degradation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Particulate matter is mainly composed of carbon with some inorganic materials and adsorbed hydrocarbons, SO x , and water, and its composition influences the catalytic activity, as well as the synthesis conditions . The reduction of this type of species is not easy but completely necessary since the small diameter makes them dangerous for human health . Although the diesel oxidation catalyst (DOC) is able to reduce the amount of particulate matter, the almost complete soot combustion is carried out over the diesel particulate filter (DPF). , This monolithic system consists of small axial parallel channels through which the gas can flow, whereas the particles are retained onto the surface and in the porosity of the channel walls. As a consequence, the pressure loss increases, and the regeneration by increasing the temperature is required.…”
Section: Introductionmentioning
confidence: 99%
“…Any activity degradation, whether it is due to hydrothermal surface modification or a loss of active potassium, will be detected as an increase in the soot oxidation temperature. To closely mimic the real conditions experienced by a DPF on a diesel engine, "loose" soot contact was achieved by a flame soot deposition technique as described elsewhere [31,79]. Klearol ® white mineral oil with~1 ppm sulfur was used as the fuel oil for soot generation.…”
Section: Methodsmentioning
confidence: 99%